Clinical Profile and Proportion of Children with Glaucoma and Glaucoma Suspect at a Tertiary Eye Care Center in Uttar Pradesh - Rizwan Ahmad Siddiqui; Sadhavi Singh; Suraj; Akanksha Yadav; Subhash Chandra Saroj (Asian Journal of Medical Research, 2023)
Background: A rare paediatric condition called paediatric glaucoma often results in severe vision loss. It consists of a variety of disorders that can be divided into primary, secondary, and acquired subtypes leading to optic neuropathy and visual field changes. To investigate the incidence and clinical features of paediatric glaucoma in a tertiary eye centre in Uttar Pradesh. Subjects and Methods: In this prospective and descriptive study, a total of 133 children aged 0 to 16 years who came to the clinic because of a diagnosis of glaucoma or suspicion of glaucoma were included. A detailed history of prenatal period, birth history including birth weight, birth trauma, delayed crying at birth, or hospitalisation for more than 48 hours was obtained. The comprehensive eye examination included visual acuity assessment, gonioscopy, intraocular pressure (IOP) measurement, and assessment of the anterior and posterior segments of the eye. Results: The majority of secondary glaucomas were those associated with traumatic glaucoma (56.52%), then those associated with acquired conditions like trauma and steroid-induced glaucoma (19.57%), ANRIDIA was 10.87%, Peters anomaly and Silicon oil induce glaucoma was 4.35%, angle recession and lens induce glaucoma was 2.17%, and finally those associated with acquired conditions like lens and angle recession induce glaucoma. The primary glaucoma, which made up 42.86% of all cases of juvenile glaucoma, was the most prevalent kind. The kids with glaucoma ranged in age from 0 to 16 years old. Conclusion: In this study, primary glaucoma, which accounted for 42.86% of all juvenile glaucoma cases, and secondary glaucomas were traumatic glaucomas (56.52%). Males were more commonly affected (73.24%), with a male-to-female ratio of 2.91.